If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-38x + 32) = -43(-21 + 8x) Reorder the terms: 8(32 + -38x) = -43(-21 + 8x) (32 * 8 + -38x * 8) = -43(-21 + 8x) (256 + -304x) = -43(-21 + 8x) 256 + -304x = (-21 * -43 + 8x * -43) 256 + -304x = (903 + -344x) Solving 256 + -304x = 903 + -344x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '344x' to each side of the equation. 256 + -304x + 344x = 903 + -344x + 344x Combine like terms: -304x + 344x = 40x 256 + 40x = 903 + -344x + 344x Combine like terms: -344x + 344x = 0 256 + 40x = 903 + 0 256 + 40x = 903 Add '-256' to each side of the equation. 256 + -256 + 40x = 903 + -256 Combine like terms: 256 + -256 = 0 0 + 40x = 903 + -256 40x = 903 + -256 Combine like terms: 903 + -256 = 647 40x = 647 Divide each side by '40'. x = 16.175 Simplifying x = 16.175
| 10(x+1)-4v=3(2v+3)-11 | | 3n-4=2n | | 1.1x-1.62=-1.4 | | 3x+7=7-(4x-9) | | 5.75+5-k= | | x=t^2+3t | | 800x=100x^2 | | 2(5x+3)=98+3x | | 9(8z+9)+6=-273 | | -6(x-7)-7=-7x+2 | | -2.5--0.7=x | | 1.1x=3y-0.4 | | 3p+3.7=9.1 | | -13=x+72 | | n-5=-13 | | .2(x+3)-.5(x+3)=-0.3-0.9 | | 496=62x | | 3/8c=6 | | (n-7)-2n=12 | | 10-2(x+10)=60 | | 7x-1=23+7x | | x+4.07=6.46 | | 6x+6=11-2x | | 8x-15=155 | | -b+8=-15 | | 7s=-49 | | R+(R-12)=90 | | 5x-15=155 | | 7(7x+4)=77 | | 26x-11=5(5x+3)-4 | | 0.2(p+6)-0.7(p+2)=-3 | | 9=3k-4-7k |